Millimetre wave coarse beamforming using outband sub‐6 GHz reconfigurable antennas - Oday Bshara; Vasil Pano; Md Abu Saleh Tajin; Kapil R. Dandekar (IET Communications, 2021)
Abstract Low latency beamforming using phased antenna arrays is the key for practical deployment of envisioned millimetre wave (mmWave) Gbps mobile networks. This work aims towards reducing the overhead of the exhaustive sector‐level sweep phase of the analog beamforming adopted in the IEEE 802.11ad standard. This work is the first to propose the use of reconfigurable antenna single RF chain in the sub‐6 GHz new radio (NR) band to aid codebook‐based beam selection in the mmWave band of the NR. We exploit the congruence between the spatial propagation signatures of signals at both mmWave and sub‐6 GHz frequencies to reduce the beam search space. The simulation results show a significant reduction in mmWave beam search overhead up to 70% on average and 80% with an average gain loss of 3dB.